Mismatch Negativity as a “Translatable” Brain Marker Toward Early Intervention for Psychosis: A Review - Nagai, Tatsuya; Tada, Mariko; Kirihara, Kenji; Araki, Tsuyoshi; Jinde, Seiichiro; Kasai, Kiyoto (Frontiers in Psychiatry, 2013)
Recent reviews and meta-analyses suggest that reducing the duration of untreated psychosis leads to better symptomatic and functional outcome in patients with psychotic disorder. Early intervention attenuates the symptoms of individuals at clinical high-risk (HR) for psychosis and may delay or prevent their transition to psychosis. Identifying biological markers in the early stages of psychotic disorder is an important step towards elucidating the pathophysiology, improving prediction of the transition to psychosis, and introducing targeted early intervention for help-seeking individuals aiming for better outcome. Mismatch negativity (MMN) is a component of event-related potentials that reflects preattentive auditory sensory memory and is a promising biomarker candidate for schizophrenia. Reduced MMN amplitude is a robust finding in patients with chronic schizophrenia. Recent reports have shown that people in the early stages of psychotic disorder exhibit attenuation of MMN amplitude. MMN in response to duration deviants and in response to frequency deviants reveals different patterns of deficits. These findings suggest that MMN may be useful for identifying clinical stages of psychosis and for predicting the risk of development. MMN may also be a “translatable” biomarker since it reflects NMDA receptor function, which plays a fundamental role in schizophrenia pathophysiology. Furthermore, MMN-like responses can be recorded in animals such as mice and rats. This article reviews MMN studies conducted on individuals with HR for psychosis, first-episode psychosis, recent-onset psychosis, and on animals. Based on the findings, the authors discuss the potential of MMN as a clinical biomarker for early intervention for help-seeking individuals in the early stages of psychotic disorder, and as a translatable neurophysiological marker for the preclinical assessment of pharmacological agents used in animal models that mimic early stages of the disorder.